Representasi Superioritas Tokoh Perempuan dalam Novel Tango dan Sadimin Karya Ramayda Akmal - Sugiarti, Sugiarti; Sari, Suci Puspita; Anggraini, Purwati (Jurnal Pembelajaran Sastra, 2021)
This study aims to describe the superiority of female characters in the novel Tango and Sadimin by Ramayda Akmal. The approach used in the study is the approach of radical feminism which emphasizes the superiority of women in the reality of literary works. The data source of this study is the novel Tango and Sadimin by Ramayda Akmal. The research data is in the form of story units or story sequences related to the superiority of female characters in the novel. Data analysis technique is done by content analysis through data reduction, data presentation, and conclusion drawing stages as the final stage of the study. The results of the study are as follows. First, the form of superiority of women in the public sphere is characterized by all the activities carried out outside the home that are earning a living to make ends meet, establishing cooperation to build a business, being able to live independently, and becoming the backbone of the family. Secondly, the superiority of women in the domestic realm is illustrated through women's responsibilities in taking care of the household, caring for and giving love, and being able to guide their children to become a better person.